2018
DOI: 10.1128/msystems.00009-18
|View full text |Cite
|
Sign up to set email alerts
|

Genome Reduction in Psychromonas Species within the Gut of an Amphipod from the Ocean’s Deepest Point

Abstract: As a unique but poorly investigated habitat within marine ecosystems, hadal trenches have received interest in recent years. This study explores the gut microbial composition and function in hadal amphipods, which are among the dominant carrion feeders in hadal habitats. Further analyses of a dominant strain revealed genomic features that may contribute to its adaptation to the amphipod gut environment. Our findings provide new insights into animal-associated bacteria in the hadal biosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…In contrast, we found that TMAO reductase (torECAD), which reduces TMAO to TMA, was not present in any of the piezophilic Colwellia. A similar finding has been noted in genomes of Psychromonas from the guts of hadal amphipods, where the lack of TMAO reductase was attributed to the preferential need for TMAO as a piezolyte in the host amphipod over its use as an electron acceptor by the microbe [153]. An alternative hypothesis is that TMAO is used by microbial piezophiles as a piezolyte as it is in deep-sea metazoans [147,148].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, we found that TMAO reductase (torECAD), which reduces TMAO to TMA, was not present in any of the piezophilic Colwellia. A similar finding has been noted in genomes of Psychromonas from the guts of hadal amphipods, where the lack of TMAO reductase was attributed to the preferential need for TMAO as a piezolyte in the host amphipod over its use as an electron acceptor by the microbe [153]. An alternative hypothesis is that TMAO is used by microbial piezophiles as a piezolyte as it is in deep-sea metazoans [147,148].…”
Section: Discussionsupporting
confidence: 73%
“…Finding differences in respiratory capacity within piezophiles is not unexpected. Others have previously noted the influence of collection depth and pressure on the presence and regulation of respiratory membrane-bound cytochrome c oxidases and hydrogenases [ 22 , 72 , 92 , 132 , 140 , 141 , 144 , 145 , 153 ]. These changes could stem directly from pressure influences or from a greater reliance on the colonization of reduced oxygen niches associated with particles or animals [ 15 , 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous marine isolates of Verrucomicrobiae and Oceanospirillaceae (dominant family of Oceanospirillales in our study) were aerobes with broad substrate spectra (including monosaccharides, amino acids, alcohols, organic acids), and some Oceanospirillaceae additionally perform nitrate reduction ( 36 , 37 ). Opitutae , Psychromonadaceae (dominant family of Alteromonadales ), and BD7-8 subgroup commonly live in symbiotic relations with marine sediment invertebrates and are facultatively anaerobic carbohydrate degraders ( Opitutae , Psychromonadaceae ) or putatively chemoautotrophic, aerobic sulfide oxidizers (BD7-8) ( 38 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…A Psychromonas strain (CNPT3) has been isolated from the gut of a decaying amphipod collected at a depth of 5,700 m in the North Pacific Ocean (21), suggesting a close relationship between Psychromonas and amphipods in certain deep-sea habitats. In a more recent study of the amphipod gut microbiota from the Mariana Trench, the draft genome of a Psychromonas strain (CDP1) was analyzed, which revealed a significant genome reduction driven by host association (22). Members of the genus Propionibacterium were found in the gut of the bark beetle Dendroctonus rhizophagus and are persistent in all life stages of this insect (23).…”
Section: Discussionmentioning
confidence: 99%